Severe and Moderate Acute Malnutrition Can Be Successfully Managed with an Integrated Protocol in Sierra Leone. Issue 11 (30th September 2015) - Maust, Amanda; Koroma, Aminata S; Abla, Caroline; Molokwu, Nneka; Ryan, Kelsey N; Singh, Lauren; Manary, Mark J
Abstract: Background: Global acute malnutrition (GAM) is the sum of moderate acute malnutrition (MAM) and severe acute malnutrition (SAM). The use of different foods and protocols for MAM and SAM treatment can be cumbersome in emergency settings. Objective: Our objective was to determine the recovery and coverage rates for GAM of an integrated protocol with a single food product, ready-to-use therapeutic food (RUTF), compared with standard management. Methods: This was a cluster-randomized controlled trial in Sierra Leone conducted in 10 centers treating GAM in children aged 6–59 mo. The integrated protocol used midupper arm circumference (MUAC) as the criterion for admission and discharge, with a MUAC <12.5 cm defining malnutrition. The protocol included a decreasing ration of RUTF and health maintenance messages delivered by peers. Standard therapy treated MAM with a fortified blended flour and SAM with RUTF and used weight-for-height to determine admission to the treatment program. Coverage rates were the number of children who received treatment/number of children in the community eligible for treatment. Results: Most of the children receiving integrated management had MAM (774 of 1100; 70%), whereas among those receiving standard management, SAM predominated (537 of 857; 63%; P = 0.0001). Coverage was 71% in the communities served by integrated management and 55% in the communities served by standard care ( P = 0.0005). GAM recovery in the integrated management protocol was 910 of 1100 (83%) children and was 682 of 857 (79%) children in the standard therapy protocol. Conclusion: Integrated management of GAM in children is an acceptable alternative to standard management and provides greater community coverage. This trial was registered at clinicaltrials.gov as NCT01785680.